Analisis Eksternalitas Pertambangan Pasir di Kabupaten Tegal Provinsi Jawa Tengah - Suci Aini Suryaning Pertiwi; Shita Paramuditaningtyas (Fakultas Teknik dan Rekayasa, 2022)
Indonesia is a developing country with abundant natural resources, both living and non-living natural resources. Natural resources have an important role for the progress of an area. Based on natural resources, it is divided into two, namely renewable and non-renewable natural resources. One of the non-renewable natural resources is mineral resources which are utilized by way of mining. One of the activities carried out in Pangkah Subdistrict, Tegal Regency caused externalities to the environment, social and economy of the community. The positive impact felt by the community is an increase in income. However, in reality the negative impact is more dominant in the form of visible externalities, namely environmental damage. What can be recommended is reinstating sand permits in the form of enforcing mining business licenses and forming groups concerned with the environment to develop the local community's economy. Keywords: Sand Mining, Externalities, Policy.